2020
DOI: 10.1371/journal.ppat.1008852
|View full text |Cite
|
Sign up to set email alerts
|

The glucosyltransferase activity of C. difficile Toxin B is required for disease pathogenesis

Abstract: Enzymatic inactivation of Rho-family GTPases by the glucosyltransferase domain of Clostridioides difficile Toxin B (TcdB) gives rise to various pathogenic effects in cells that are classically thought to be responsible for the disease symptoms associated with C. difficile infection (CDI). Recent in vitro studies have shown that TcdB can, under certain circumstances, induce cellular toxicities that are independent of glucosyltransferase (GT) activity, calling into question the precise role of GT activity. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…However, TcdB becomes inaccessible to antibodies after entering the host cells. We found that mutations that selectively disrupt GTPases binding drastically reduced the cytopathic toxicity of TcdB holotoxin, which is consistent with prior studies showing that a glucosyltransferase-deficient TcdB mutant was atoxic in vivo ( 50 ). Therefore, the GTD is an ideal molecular target for therapeutic interventions once the toxin is inside the cells, which will directly target the root cause of disease symptoms and cellular damage.…”
Section: Discussionsupporting
confidence: 91%
“…However, TcdB becomes inaccessible to antibodies after entering the host cells. We found that mutations that selectively disrupt GTPases binding drastically reduced the cytopathic toxicity of TcdB holotoxin, which is consistent with prior studies showing that a glucosyltransferase-deficient TcdB mutant was atoxic in vivo ( 50 ). Therefore, the GTD is an ideal molecular target for therapeutic interventions once the toxin is inside the cells, which will directly target the root cause of disease symptoms and cellular damage.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the DxD TcdB has been used in vitro and ex vivo to demonstrate the glucosyltransferase-independent mechanism for TcdB-induced necrotic cell death (17)(18)(19). It is unclear how 50 mg of DxD TcdB failed to produce significant epithelial injury in the present model, but a recently published report shows isogenic spores lacking glucosyltransferase activity have minimal, if any, colonic inflammation in C. difficile infected mouse and hamster models (41). This could be the result of species-specific differences.…”
Section: Discussionmentioning
confidence: 79%
“…However, these systems may have lacked the sensitivity of the C. difficile infection model, in which toxins are constantly produced and interact with the host epithelium over a course of several days. Recently, GT activity of TcdB was shown to be necessary to cause CDI, and there were no observed GTindependent effects in the mouse model of infection using defined GTX mutants in the C. difficile 630 strain [16]. This study had two limitations: the first being that the C. difficile 630 strain produces few CDI symptoms in the mouse model of infection when compared to epidemic C. difficile strains, and it also does not cause epithelial damage [16][17][18].…”
Section: Plos Pathogensmentioning
confidence: 95%
“…The relevance of GT-independent cell death during infection has been unclear since it is unknown if cells encounter the concentration of TcdB required to stimulate necrotic cell death. A recent study concluded that GT activity was necessary to cause CDI in mouse and hamster models of infection, but this does not preclude an additional role for GT-independent events as the infection progresses [16]. The study also involved GT-defective C. difficile mutants in the 630 strain, which is genetically tractable, but causes only mild disease symptoms in animal models [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation